Effect of WhatsApp-based BETTER model sexual counselling on sexual function and sexual quality of life in breast cancer survivors: a randomized control trial - Shirin Nazarzadeh; Fatemeh Moghaddam-Tabrizi; Mahmonir Haghighi; Rasool Gharaaghaji-Asl (BMC, 2024)
Abstract Objective The aim of the study was to determine the effect of WhatsApp-based BETTER sex counselling on sexual function and sexual quality of life in breast cancer survivors in a randomized control trial. Methods This is a randomized controlled trial in which a total of 90 breast cancer survivors were recruited using convenience sampling and then randomly assigned to two groups of WhatsApp-based BETTER model counselling and routine care. Data collection tools consisted of a demographic questionnaire, the Sexual Quality of Life-Female (SQOL-F) and the Sexual Function Index (FSFI-BC). Participants in the intervention group were given access to the 6-week program. The program consisted of six consultation and assignment packages covering all six steps of the BETTER model. Data were analyzed using SPSS software version 20. Chi-square test, independent samples t-test and repeated measures analysis of variance were used. The significance level (p-value) was considered to be less than 0.05. Results In the control group, the mean score of SQL scale changed from 35.16 ± 10.71 to 35.16 ± 12.97 (P > 0.05) and in the intervention group, it significantly increased from 34.76 ± 10.13 to 68.20 ± 20.48 (P < 0.001). Similarly, the comparison of mean of FSF in the control group showed a none-significant change from 58.13 ± 7.11 to 58.35 ± 6.11 (P > 0.05), and in the intervention group, it significantly improved from 59.49 ± 6.10 to 120.73 ± 25.54 (P < 0.001). The results of rANOVA indicated that there was a significant difference in the mean scores of the SQL and SFS between the two groups from pre- to post-intervention, and then over the 1-month follow-up period in the intervention group (p < 0.001). Considering partial eta squared, the effect of the intervention had the highest interaction effect on both variables of the sexual function index (η2 = 0.73) and sexual quality of life (η2 = 0.41). Conclusions The intervention program was a successful model for improving female sexual quality of life and female sexual function in breast cancer survivors. Trial registration IRCT20210926052601N1, 7-11-2021.